Redox-Responsive Comparison of Diselenide and Disulfide Core-Cross-Linked Micelles for Drug Delivery Application - Sonyabapu Yadav; Kalyan Ramesh; Obireddy Sreekanth Reddy; Viswanathan Karthika; Parveen Kumar; Sung-Han Jo; Seong II Yoo; Sang-Hyug Park; Kwon Taek Lim (MDPI AG, 2023)
In this study, diselenide (Se-Se) and disulfide (S-S) redox-responsive core-cross-linked (CCL) micelles were synthesized using poly(ethylene oxide)2k-b-poly(furfuryl methacrylate)1.5k (PEO2k-b-PFMA1.5k), and their redox sensitivity was compared. A single electron transfer-living radical polymerization technique was used to prepare PEO2k-b-PFMA1.5k from FMA monomers and PEO2k-Br initiators. An anti-cancer drug, doxorubicin (DOX), was incorporated into PFMA hydrophobic parts of the polymeric micelles, which were then cross-linked with maleimide cross-linkers, 1,6-bis(maleimide) hexane, dithiobis(maleimido) ethane and diselenobis(maleimido) ethane via Diels-Alder reaction. Under physiological conditions, the structural stability of both S-S and Se-Se CCL micelles was maintained; however, treatments with 10 mM GSH induced redox-responsive de-cross-linking of S-S and Se-Se bonds. In contrast, the S-S bond was intact in the presence of 100 mM H2O2, while the Se-Se bond underwent de-crosslinking upon the treatment. DLS studies revealed that the size and PDI of (PEO2k-b-PFMA1.5k-Se)2 micelles varied more significantly in response to changes in the redox environment than (PEO2k-b-PFMA1.5k-S)2 micelles. In vitro release studies showed that the developed micelles had a lower drug release rate at pH 7.4, whereas a higher release was observed at pH 5.0 (tumor environment). The micelles were non-toxic against HEK-293 normal cells, which revealed that they could be safe for use. Nevertheless, DOX-loaded S-S/Se-Se CCL micelles exhibited potent cytotoxicity against BT-20 cancer cells. Based on these results, the (PEO2k-b-PFMA1.5k-Se)2 micelles can be more sensitive drug carriers than (PEO2k-b-PFMA1.5k-S)2 micelles.